Scholastic's The magic school bus explores inside the earth - Microsoft Home (Firm); Scholastic Inc. (New York : Microsoft Press, 1996)
Multimedia science adventure program for primary and younger elementary students. Features Ms. Frizzle and the characters from the book series as they explore the earth's landscape. Offers science reports, experiments, games, and three-dimensional exploration of the earth.
System requirements: Multimedia PC with 486SX/25MHz (33MHz recommended) or higher processor; 4MB RAM (8MB recommended); MS-DOS 5.0 or later; Windows 3.1 or later, Windows 95 or Windows NT 3.51; SVGA 256-color display monitor; eight-bit audio board (sixteen-bit recommended); hard disk with 5MB free space; double-speed CD-ROM drive; Microsoft mouse or compatible pointing device; headphones or speakers.
3-6.
K-3.
Keywords: Earth -- Internal structure -- Interactive multimedia; Geology -- Interactive multimedia; Physical geology -- Interactive multimedia